Clonally‐related primary ALK rearranged adenocarcinoma and associated metastatic lesions. Issue 7 (8th May 2018) - Zhu, You‐cai; Deng, Yun‐te; Wang, Wen‐xian; Xu, Chun‐wei; Zhuang, Wu; Du, Kai‐qi
Abstract : ALK rearrangement is a driver gene in non‐small cell lung cancer (NSCLC). ALK ‐positive tumors are sensitive to ALK‐tyrosine kinase inhibitors (TKIs). The detection of key driver genes is crucial to enable personalized treatment. Different histomorphological patterns have different driver genes. Herein, we report the case of a 42‐year‐old male patient diagnosed with adenocarcinoma with different histomorphologies in the primary lung site (mucinous type) and lymph node metastasis (solid type), of the same genotype, both presenting with ALK rearrangement but negative for EGFR mutation. This histological heterogeneity did not necessarily indicate a genomic difference. Genomic analysis may be a supplement to the histological features of ALK ‐rearranged tumors. These gene alterations could aid the choice of an appropriate TKI and predict therapeutic response.